Assumptions of organizational behaviour in different organization types - Jokūbauskienė, Saulė (Information & Media, 2016)
The field of information, knowledge society is a wide and complex area. The understanding of organisational values leads from classical economical understanding to knowledge economy concept. The intensity of nowadays society does that extremely important becomes speed and fast but qualified done exercises. As such of importance is the ability to select the required information. In the context of these processes, the creation of knowledge is understandable as a dynamic and long-lasting process. The potential of organisational behaviour in problem solving depends on qualified “knowledge workers” and common “organisational competence”. The main idea states that we now need exceptional competences and abilities for the management of digital complexity. Also, the change is of orientation to the management of processes, so the structure is less important.The subject of scientific discussions becomes the system of organisational management and organisational behaviour. The assumptions of organisational behaviour in different organisation types are various. The preconditions of organisational behaviour are the evolution of abilities and workers of digital age. The processes organisations are able to get in, makes them more effective, responsible and gives them a competitive advantage.In the article, the public and private sector organisational types of behaviour that mainly affect organisational and individual competencies and cause an effect on the results of activities and motivation are discussed. The economic, political and social changes become a new challenge for the organisations and they may live through the changes by using intellectual capital, reducing procedures, fully using technologies and making up individual motivation.
Keywords: ...